Wheat should not be double cropped with soybean in infested fields with Meloidogyne javanica - Lucas, Diego Gonçalves Ribeiro (2025)
Brazil is a major soybean producer, but wheat is less emphasized in its agriculture. Both crops face significant challenges from plant-parasitic nematodes (PPNs), which cause major yield losses, especially in soybeans. M. javanica, a root-knot nematode, is commonly found in soybean fields, causing losses of 10% to 40% depending on soil type. Wheat is also affected, with M. javanica first reported as a problem in 1964 and growth reduction observed two wheat cultivars exposed to high nematode populations in 1981. Managing M. javanica is crucial, and crop succession is a key strategy, often used by soybean farmers. In Brazil, maize is the main crop after soybean, but sorghum and pearl millet are also used in tropical and transitional regions, while wheat is common in the subtropical part. However, the response of these crops to M. javanica is not clear, with some studies showing resistance and others showing susceptibility. In addition, studies on wheat growth and development inpairment by M. javanica have focused on outdated cultivars. This dissertation aims to evaluate newer wheat cultivars susceptibility and test alternative crops for soybean succession in M. javanica infested areas.